Adipose-derived mesenchymal stem cells improve glucose homeostasis in high-fat diet-induced obese mice. Issue 1 (December 2015) - Cao, Mingjun; Pan, Qingjie; Dong, Huansheng; Yuan, Xinxu; Li, Yang; Sun, Zhen; Dong, Xiao; Wang, Hongjun
Abstract Introduction Effective therapies for obesity and diabetes are still lacking. The aim of this study was to evaluate whether a single intravenous infusion of syngeneic adipose-derived mesenchymal stem cells (ASCs) can reduce obesity, lower insulin resistance, and improve glucose homeostasis in a high-fat diet-induced obese (DIO) mouse model. Methods Seven-week-old C57BL/6 mice were fed a high-fat diet for 20 weeks to generate the DIO mouse model. Mice were given a single intravenous infusion ofex vivo expanded syngeneic ASCs at 2 × 106 cells per mouse. DIO or CHOW mice injected with saline were used as controls. Body weights, blood glucose levels, glucose, and insulin tolerance test results were obtained before and 2 and 6 weeks after cell infusion. Triglyceride (TG), high-density lipoprotein (HDL), and insulin levels in serum were measured. Expressions of genes related to insulin resistance, including peroxisome proliferator-activated receptor γ (PPARγ ) and insulin receptor (InsR ), and inflammation (IL-6, F4/80, and nucleotide-binding oligomerization domain containing 2, orNOD2 ), were measured in livers at mRNA level by real-time-polymerase chain reaction analysis. Beta-cell mass in pancrheases from CHOW, DIO, and DIO + ASC mice was quantified. GFP+ ASCs were injected, and the presence of GFP+ cells in livers and pancreases was determined. Results DIO mice that had received ASCs showed reduced body weights, reduced blood glucose levels, and increased glucose tolerance. ASC treatment was found to reduce TG levels and increase serum HDL levels. In livers, less fat cell deposition was observed, as were increased expression of InsR and PPARγ and reduction in expressions of IL-6 and F4/80. Treated mice showed well-preserved pancreatic β-cell mass with reduced expression of F4/80 and TNF-α compared with DIO controls. GFP+ cells were found in liver and pancreas tissues at 1 and 2 weeks after cell injection. Conclusions ASC therapy is effective in lowering blood glucose levels and increasing glucose tolerance in DIO mice. The protective effects of ASCs arise at least in part from suppression of inflammation in the liver. In addition, ASCs are associated with better-preserved pancreatic β-cell mass.